2007
DOI: 10.1038/sj.npp.1301645
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Hypoexcitability in Chronic Smokers? A Transcranial Magnetic Stimulation Study

Abstract: Studies in animal models and humans indicate that chronic nicotine intake influences neuronal excitability, resulting in functional and structural CNS changes. The aim of the present study was to explore human primary motor cortex (M1) excitability with transcranial magnetic stimulation (TMS) in chronic smokers. A total of 44 right-handed volunteers, aged 20-30 years, participated in the study. Chronic smokers were compared with age-and sex-matched healthy nonsmokers. We tested cortical excitability with singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 36 publications
(39 reference statements)
5
48
1
1
Order By: Relevance
“…Foregoing investigations of motor-cortex excitability with TMS have shown a reduction in intracortical facilitation, prolonged CSP durations, enhanced short-afferent inhibition (SAI), and reduced aMEPs, indicating cortical hyopexcitability in chronic healthy smokers during nicotine withdrawal (Grundey et al, 2013;Lang et al, 2008). However, the duration of nicotine withdrawal differed between the studies, ranging from one to six (Grundey et al, 2013) hours.…”
Section: Smoking Effect On Cortical Excitabilitymentioning
confidence: 92%
See 1 more Smart Citation
“…Foregoing investigations of motor-cortex excitability with TMS have shown a reduction in intracortical facilitation, prolonged CSP durations, enhanced short-afferent inhibition (SAI), and reduced aMEPs, indicating cortical hyopexcitability in chronic healthy smokers during nicotine withdrawal (Grundey et al, 2013;Lang et al, 2008). However, the duration of nicotine withdrawal differed between the studies, ranging from one to six (Grundey et al, 2013) hours.…”
Section: Smoking Effect On Cortical Excitabilitymentioning
confidence: 92%
“…Further investigations on chronic smokers during nicotine withdrawal revealed unaffected LTD-like plasticity following cathodal tDCS, which was abolished following nicotine reapplication (Grundey et al, 2012b). Moreover, physiological investigations with transcranial magnetic stimulation (TMS) indicate that chronic smoking tilts the balance between facilitation and inhibition towards cortical hypoexcitability (Grundey et al, 2013;Lang et al, 2008). In summary, evidence points to a significant modulation of both neuroplasticity and cortical excitability through acute and chronic nicotine intake in healthy smokers and nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…12, 13 Lang and colleagues 12 investigated chronic smoker excitability with single and paired pulse TMS to the left primary motor cortex as well as short latency afferent inhibition by combining median nerve stimulation and motor cortex TMS. They found that, compared with nonsmoking controls, chronic smokers showed a significantly larger amount of short latency afferent inhibition, which is thought to depend on the activity of cholinergic inhibitory circuits produced by somatosensory inputs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lang and colleagues 12 reported corticospinal hypoexcitability in chronic smokers. On the other hand, increased corticospinal excitability in chronic smokers during nicotine withdrawal compared to nonsmokers was recently reported in another study.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are needed to explore the effects in these subject groups. Moreover, apart from other confounding factors like age (Floel et al, 2008), tobacco smoking (Lang et al, 2008b), and genetics (Cheeran et al, 2008), altered dopamine levels in patients should be borne in mind when brain stimulation protocols are applied for diagnostic or therapeutic purposes.…”
Section: General Remarksmentioning
confidence: 99%